Optimizing Impact in Fighting the Global HIV Epidemic - Ritz, Derek; Ketani, Violet (International Journal of Population Data Science, 2018)
Introduction Linking healthcare expenditure data with health outputs and outcomes data is challenging. This is especially true in low-resource (LMIC) settings. Where such linking can be accomlished, however, it supports the development of IMPACT-per-DOLLAR metrics that may be leveraged to support programme optimization. Objectives and Approach This session will describe a new data-linking design for a global health programme targeted to low and middle-income countries (LMIC). The US Government's President's Emergency Plan for AIDS Relief (PEPFAR; www.pepfar.gov) is a $7 billion/year programme spanning 58 LMICs. PEPFAR prepares annual budgets and plans. On a quarterly basis, Implementing Partners report programmatic district-level Monitoring, Evaluation and Reporting (MER) indicators to a central database. Starting in July, 2018, quarterly expenditure data will also be captured, broken down by major programme area and high level account code. The novel new data-linking approach triangulates the budget, indicator and expenditure datasets. Results The PEPFAR programme is managed by the US State Department's Office of the Global AIDS Coordinator (S/GAC). S/GAC undertook, in 2017, a significant re-design of its information system requirements and the software systems that will support these. A multi-year design and prototyping effort has yielded a novel new approach for financial monitoring intended to improve S/GAC's abilities to exert its mandates regarding both programmatic and financial oversight. The new data-linking solutions are being implemented across all PEPFAR countries during the first half of 2018. Information model design choices (and trade-offs), solution architecture designs, and preliminary pilot results of this new implementation will be reported at the confernce. A discussion of implementation science lessons-learned specific to deploying in LMICs will also be presented. Conclusion/Implications PEPFAR's goal and mission is to operationalize HIV epidemic control and achieve an AIDS-free generation by 2030. Data analytics are proving essential to achieving this goal. S/GAC's re-design efforts will help better link its huge financial and programmatic (MER) datasets to support DALY-per-DOLLAR impact optimization on this important initiative.